Revitalisasi Pendidikan Sains Melalui Pendekatan Islamisasi - Mulyani, Sri; Wahyuni, Andi Eki Dwi; Usman, Syahruddin; Saprin, Saprin (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This article reviews the importance of revitalizing science education through an Islamization approach as an effort to integrate Islamic values ​​in modern science. By emphasizing the concept of integration between religion and science, this approach aims to overcome the dichotomy between religious science and secular science. The research method used is a literature review, involving analysis of theories and practices related to the Islamization of science proposed by figures such as Syed Muhammad Naquib al-Attas and Ismail Raji al-Faruqi. The Islamization of science is considered capable of enriching science education with a holistic perspective that includes moral and spiritual dimensions, thereby creating a generation of scientists who are not only intellectually superior, but also have ethical awareness. The main challenges to this approach involve the dominance of the secular science paradigm in education and the need to develop methodologies that are in line with Islamic principles. This article recommends developing a curriculum based on Islamic values ​​and global collaboration to strengthen the position of Islamic science in the international arena.